THE 2 DIMENSIONAL VERTICAL HYDRODYNAMIC MODEL IN KAPUAS KECIL RIVER, PONTIANAK, WEST BORNEO - UTAMIPUTERI (NIM: 12908007); pembimbing: Dr.rer.nat. Mutiara Rachmat Putri, ISWIATI
Study of current toward the density distribution in the Kapuas Kecil River was performed using 2 dimensional vertical (2DV) hydrodynamic model with positive estuarine mode developed by Kämpf (2010). The simulation was driven by tidal elevation and density gradient on 1- 20 July 2010. The results show that the density in river body for 20 days ranged between 1000.2-1006.7 kg/m3 in the estuary and around 1000.0 – 1004.1 kg/m3 in the branch meetings of Kapuas Kecil River and Landak River. Density values at the surface and bottom of estuary were 1002.15 kg/m3 and 1004.59 kg/m3. From the field data obtained at the estuary, the temperature obtained was 28.3°C and the salinity was 0 ppt, resulting in a surface density of 996.05 kg/m3. At the branch meetings between Kapuas Kecil River and Landak River, simulation result of density value is 1000 kg/m3 which shows a salinity of 0 ppt, while the surface density of field observations at a temperature of 27.7°C and salinity 0 ppt is 996.23 kg / m3. Respectively, at the time of spring and neap tide, tidal effects can reach 20.3 km and 11.2 km, from the sea. Water with a density of 1002 kg/m3 can reach up to 11.2 km from the sea at spring, and 4.2 km at neap. Tidal asymmetry between Karimata Strait and the shallow water bodies is indicated by the time taken from the low tide conditions towards the highest tides (10 hours) being much faster than the time it takes from the highest tide conditions towards low tide (14 hours) at spring. During neap tide, the time taken from low tide conditions towards the highest tides (15 hours) is much slower than the time taken from the highest tide conditions towards low tide (9 hours).